Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1526924816679844
|View full text |Cite
|
Sign up to set email alerts
|

Communicating About Choices in Transplantation (COACH)

Abstract: Results provide preliminary support for the program's impact. Moreover, participant evaluations of the COACH were overwhelmingly positive. A more definitive program evaluation with a larger, more diverse sample is currently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Furthermore, African Americans report less communication regarding information about transplantation from their physicians [21, 22]. Studies have found that poor patient-provider communication and family-provider communication contributes to the lower level of knowledge regarding the benefits of kidney transplantation in African Americans [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, African Americans report less communication regarding information about transplantation from their physicians [21, 22]. Studies have found that poor patient-provider communication and family-provider communication contributes to the lower level of knowledge regarding the benefits of kidney transplantation in African Americans [23]. …”
Section: Discussionmentioning
confidence: 99%
“…11 Third, candidates and their families may have, or perceive they have, limited social networks or individuals that they feel comfortable approaching about living donation. [12][13][14] Fourth, there may be social or financial limitations on an individual's ability to pursue living donation. [15][16][17][18] And fifth, transplant teams may variably support the option of living donation for their patients, such that the option is not offered at their center or even region.…”
Section: Introductionmentioning
confidence: 99%
“…Second, evidence exists from this population that some patients and potential donors may have general mistrust of the medical community and therefore seek to avoid an additional surgery . Third, candidates and their families may have, or perceive they have, limited social networks or individuals that they feel comfortable approaching about living donation . Fourth, there may be social or financial limitations on an individual's ability to pursue living donation .…”
Section: Introductionmentioning
confidence: 99%
“…5 These discussions are vital to the process of organ donation, as they increase the likelihood of finding potential donors and talking about LDKT with clinicians, each of which may lessen the need for dialysis, reduce the duration of dialysis, and decrease the wait time for a transplantable kidney. [6][7][8][9][10][11][12][13][14] Discussing LDKT with family or friends may also facilitate patients' receipt of desired or needed support for the complex treatment decisions they face, result in the recruitment of living donor champions, provide opportunities to process information and voice concerns, and benefit both physical and mental health. [13][14][15][16][17][18][19] Further, communication is a modifiable social process or behavior that can be targeted as a strategy for increasing LDKT.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Discussing LDKT with family or friends may also facilitate patients' receipt of desired or needed support for the complex treatment decisions they face, result in the recruitment of living donor champions, provide opportunities to process information and voice concerns, and benefit both physical and mental health. [13][14][15][16][17][18][19] Further, communication is a modifiable social process or behavior that can be targeted as a strategy for increasing LDKT. 10,13,14 Extant research on LDKT discussions with family or friends, however, is limited and has often concentrated on donation requests.…”
Section: Introductionmentioning
confidence: 99%